TRANSFORMASI HEWAN KARNIVORA SEBAGAI REFLEKSI MEGALOMANIA DALAM SENI GAMBAR - ABADI, PRIANDOKO (Arty: Jurnal Seni Rupa, 2015)
Desire man to absolutely and indefinite control living creatures, either animal or a fellow human being made him as if return to natural conditions.In the end people may dianalogikan is located with animals and free from financial burdens.This gave rise to the assumption that man having the nature of megalomania.Pertaining to the theme the purpose of making the project the study expressing the idea writer of the nature of megalomania in humans through the form of transformation carnivorous animal in the work of the arts of drawing.As well as to create a number of 10 work of a having subject matter megalomania in the style of fantasy a realistic.The creation of the work of the process in a project to this study through direct observation in their surroundings writer , shooting a model pictures as well as the actual shot on the internet correspond with an idea who writers want , making sketches , until pendetailan an image on paper through mixed medium. Writer has made ten work of a.Size work produced that is 60 cm x 42 cm.A style in the arts of drawing who writers included is style fantasy a realistic themes social.Specifically subject matter in real life project the study describe reality life such as pride, racism, corruption, oppression, war, and murder occurring in the national and international..In realizing change of form in animals carnivorous, the writers using a technique transformation a domineering manner, distortion and deformation.